A Polyphonic Debate on the “Modern” Public Budget in Brazil and its Implications for Accounting - Bartoluzzio, Alann Inaldo Silva de Sá; Cruz, Cláudia Ferreira da; Dias, Lidiane Nazaré da Silva; Diniz, Josedilton Alves; Sauerbronn, Fernanda Filgueiras (Advances in Scientific and Applied Accounting, 2023)
Objective: To produce an essay from different perspectives on the budgetary debate in Brazil to articulate the field with issues involving the public budget and its social, political, institutional, academic implications, among others. Method: In a constructivist perspective, researchers with different onto-epistemic bases developed reflections based on their previous theoretical and practical experiences. This material was articulated in two debates with the interested community, the first being held at the XVI Anpcont and the second mediated by the Management and Accountability Observatory (OGA/UFRJ). Based on these meetings, six perspectives on the budget debate were structured and proposed for the construction of a comprehensive discussion on the public budget in Brazil. Results: The integration of different views allowed the production of a broad, plural and multiparadigm debate on issues that touch the public budget. Nevertheless, the theoretical, conceptual and methodological integration based on a collaborative process, as proposed in this essay, enables the construction of other meanings not only for the budget, but, above all, for the accounting in/of governments. Contributions: We hope that this initiative will be recognized as comprehensive and conciliatory for the theoretical, conceptual and practical development of the government budget and public accounting, and that, based on this material, the community will find possibilities for integration, articulation and engagement for the advancement of the ongoing debate.